The Prediction of Marital Disaffection based on Developmental Family Function and the Comparison of These Variables in the Couples of Employed Group and Unemployed Group(Housewives) in Ilam City (European Journal of Behavioral Sciences, 2020)
The purpose of this study was to predict marital disaffection based on developmental family function and compare these variables in couples in employed and unemployed groups in Ilam city. The present study is correlational with respect to its purpose and implementation method. The statistical population of this study is all couples referring to counseling centers of Ilam city during winter 2017. Based on convenience sampling method, first of all, among the couples who were eager to participate in the study with the necessary qualifications such as 1) at least having high school diploma 2) age range from 20 to 40 3) passing of at least one year of marriage, 248 couples (124 women and 124 men) with the necessary qualifications were selected for this study. The instruments used in this study were the Marital Disaffection Scale (Painez, 1996) and Family Function Questionnaire (Epestin et al, 1983). Inferential statistics (independent sample T-test, multivariate analysis of variance (MANOVA), Pearson correlation coefficient and Multivariate analysis of regression were used to analyze the data. The results of this study showed that there are reverse and significant relationship between marital disaffection and developmental family function at a 95% confidence level. Also, in the second hypothesis, there is a significant difference between the mean of six components of developmental family function in couples of employed and unemployed groups. According to the results, the mean of six components in couples of employed group is higher than the unemployed group. The results of the third hypothesis of the study which suggest that there is a significant difference between the mean of marital disaffection in the two groups of employed and unemployed is accepted. The mean marital disaffection in the couples of the unemployed group is higher than the couples of the employed group. Therefore, the variable of developmental family function predicts couples’ marital disaffection.